Antibacterial activity of the organic extracts of stem bark of Cinnamomum aromaticum nees - Hoque, Md Anarul; Khatun, Mst Afroza; Islam, Rezuanul; Shekhar, Hossain Uddin; Haque, Md Enamul; Hasan, AKM Mahbub (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/dujps.v13i2.21904 Dhaka Univ. J. Pharm. Sci. 13(2): 221-224, 2014 (December)